Problems in translating musical elements in African American poetry after 1950 - Kočan, Kristina (ELOPE (Ljubljana), 2009)
In most cases, African American poetry eschews traditional literary norms. Contemporary African American poets tend to ignore grammatical rules, use unusual typography on many occasions, include much of their cultural heritage in their poetry, and interweave musical elements into literary genres. The influence of such musical genres as jazz, blues, soul, and gospel, together with the dilemmas that occur for the translator, will be shown to great extent, since music, like black speech, is a major part of African American culture and literature. The translator will have to maintain the specific African American rhythm, blues adaptations and the improvisational language under the jazz impact. The paper presents the problems in translating post-1950 African American poetry into Slovene, and asks to what extent can one successfully transfer the musical elements within this poetry for the target culture? Inevitably, it will identify a share of elements that are lost in translation.
Keywords: African American poetry; afriško ameriška poezija; American literature; American poetry; ameriška književnost; ameriška poezija; blues; ciljna kultura; gospel; izvirna kultura; jazz; prevajanje; soul; source culture; target culture; translation